Pulmonary thromboembolism in conjunction with intracavitary thrombus caused by severe acute respiratory syndrome coronavirus-2 infection in a patient living with human immunodeficiency virus - Silva,Ana Carolina Veronese (2021)
Abstract Approximately one-third of patients with coronavirus disease 2019 (COVID-19) present with coagulation disorders and hematological changes. However, the clinical manifestations of COVID-19 and prognoses of people living with human immunodeficiency virus (HIV) remain controversial. This study reports the case of a 27-year-old HIV-infected man who regularly used antiretroviral medications, had no other comorbidities and was admitted for acute respiratory distress syndrome caused by COVID-19. Complementary examinations during hospitalization revealed a diagnosis of pulmonary thromboembolism in association with an intracavitary thrombus.